Fecal microbiota transplantation in the obesity treatment - a literature review - Monika Sroczyńska; Aleksandra Żaczek; Anna Luchowska (Kazimierz Wielki University, 2023)
Introduction The World Health Organization (WHO) recognizes obesity as one of the ten most important threats affecting human health. The occurrence of obesity has been found to be closely linked to the phenomenon of intestinal dysbiosis. Fecal microbiota transplantation (FMT) can be an effective method of modifying and normalizing the composition of the intestinal microbiota. It involves the insertion of stool from a healthy donor into the recipient's digestive tract. Studies have found that FMT is effective in a wide range of diseases, but the evidence for its use in obesity treatment is limited.   Aim of the study The purpose of the study was to examine the efficacy of fecal microbiota transplantation in the treatment of obesity.   Materials and methods A search was conducted using PubMed database. Articles were searched in English using the following key words: fecal microbiota transplantation, gut microbiota, obesity.   Results FMT from lean donors had no effect on weight loss in obese individuals. However, the procedure may help reduce abdominal obesity, especially in women. Studies present mixed results in terms of changes in insulin sensitivity, but most of them demonstrate the lack of effect on it. Metabolic parameters, resting energy expenditure, caloric intake and obesity markers remained unchanged. Lower HbA1c levels were observed in patients at week 6 after FMT, although this effect was temporary. Patients' quality of life after FMT did not change. No major side effects have been reported.   Conclusion The findings suggest that fecal microbiota transplantation from lean donors does not contribute to weight loss in obese patients. Although FMT is ineffective for treating obesity, it can reduce visceral fat, particularly in women.